Patient's Right to Obtain The Electronic Medical Record Contents in Therapeutic Contract According to Indonesian Civil Law Perspective - Anggra Yudha Ramadianto (West Science Law and Human Rights, 2023)
The relationship between patients and health care providers is a contractual relationship. Health service providers have obligations to patients, one of which is to maintain medical records in health services. This obligation arises as a form of fulfilling the patient's right to obtain the contents of the medical record. The results showed that fulfilling the patient's right to obtain the contents of the record is one of the achievements in the form of giving something in a therapeutic contract. Meanwhile, violation of the fulfillment of these rights in a therapeutic contract is an unlawful act, so that this matter can be sued based on the provisions in Article 1365, 1366, and 1367 of the Indonesian Civil Law. However, based on the provisions of Article 1865 of the Indonesian Civil Law, the burden of proof in lawsuits against the law is borne by the patient as the litigant.